FORMULATION AND EVALUATION OF FENOVERINE FLOATING TABLETS - V, RASHMITHA; RAO Y, MADHUSUDAN; S, PAVANI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The purpose of this research was to develop a fenoverine gastroretentive drug delivery system which, following oral administration should have the ability to enhance and prolong the period of gastric residence time (GRD) with the desired in vitro release profile. Methods: In the present study, fenoverine floating tablets were prepared using an effervescent method using sodium bicarbonate and citric acid as a gas-generating agent. The tablets were formulated using direct compression technology using xanthan gum and sodium alginate as polymers. Pre-compression powders were evaluated for angle of repose, bulk density, tapped density, Carr’s index, and Hausner’s ratio, and the prepared tablets were evaluated for weight variation, thickness, diameter, hardness, friability, drug content, floating lag time, total floating time, and in vitro dissolution studies. The formulations were optimized for the different concentrations of xanthan gum, sodium alginate, and their combinations. Results: All the prepared formulations showed well in vitro buoyancy. The tablets remained buoyant for 6–12 h. The in vitro drug-release pattern of fenoverine floating tablets was adapted to different kinetic models with the highest regression to zero-order and Korsmeyer-Peppas, and the mechanism was found to be a Fickian mechanism. Conclusion: Out of all the formulations prepared, in vitro dissolution studies of the F4 formulation were found to be maximum than other batches, which exhibited desired sustained release time followed by acceptable floating properties.